Dziecko wobec świata pracy i zawodów. Emiryczne przyczynki. Obraz fenomenu - Piorunek, Magdalena (Wydawnictwo Naukowe UAM, 2010)
The text “Dziecko wobec świata pracy i zawodów. Emiryczne przyczynki. Obraz fenomenu” [A Child and a World of Work and Occupations. Empirical Contributions. A Picture of the Phenomenon] analyses how children perceive the specificity of the vocational world in the context of the classical theories that see a career development as a lifelong experience (Ginzberg, Super) and some selected theories that assign to this biographical stage a role in further relations with the occupational market (e.g. Roe, Gottfredson). Some selective references were made to the author’s own research project that focuses on verifying a descriptive and evaluative image of the occupational world that is formed in the childhood and wishful occupational projects of this stage that are embedded in the fantasy and in the incomplete and fragmentary knowledge that a few year old child has on the outside occupational world that it experiences indirectly. These deliberations are treated as a contribution to an analysis and description of the childhood’s development regularities; they are also a pretext for formulating general practical recommendations aimed at supporting occupational development at this stage.
A Child and a World of Work and Occupations. Empirical Contributions. A Picture of the Phenomenon